ChemInform Abstract: Highly Stereoselective Domino Oxa‐Michael/Aza‐Michael/Cyclization: Synthesis of Bicyclic Lactams and Spirooxindole Skeleton. Issue 14 (March 2016) - Le Goff, Ronan; Sanselme, Morgane; Lawson, Ata Martin; Daich, Adam; Comesse, Sebastien
Abstract: Bicyclic lactams such as (III) are readily available in the presence of 0.9‐1.2 equiv.